2015
DOI: 10.1177/0284185114536156
|View full text |Cite
|
Sign up to set email alerts
|

Individually adapted tube current selection and contrast medium injection protocol of coronary CT angiography based on test bolus parameters: a feasibility study

Abstract: It is feasible to individually adapt tube current and contrast injection protocol of CCTA based on the information of test bolus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
(43 reference statements)
1
7
0
Order By: Relevance
“…proposed algorithm is slightly influenced by TB study protocols, but 8 HU mis-estimations in coronary enhancement are negligible during CCTA. We did not find that age or BMI had an influence on this TB-based CEP algorithm, which is consistent with the findings of TB-based CEP algorithms proposed by Zhu et al [10] and Korporaal et al [11]. This could be explained by the fact that PEDAo and PTAAo, which are partially determined by patient-related factors including age, body weight, BMI, and heart rate, had been accounted for in the CEP algorithms.…”
Section: Cviasupporting
confidence: 90%
See 4 more Smart Citations
“…proposed algorithm is slightly influenced by TB study protocols, but 8 HU mis-estimations in coronary enhancement are negligible during CCTA. We did not find that age or BMI had an influence on this TB-based CEP algorithm, which is consistent with the findings of TB-based CEP algorithms proposed by Zhu et al [10] and Korporaal et al [11]. This could be explained by the fact that PEDAo and PTAAo, which are partially determined by patient-related factors including age, body weight, BMI, and heart rate, had been accounted for in the CEP algorithms.…”
Section: Cviasupporting
confidence: 90%
“…A clinical study [19] observed that the correlation between aortic peak enhancement and cardiac output was superior to the correlation with body weight. Cardiac output is closely related to the time-attenuation curve obtained from a TB injection [10,20]. Zhu et al [10] held the view that cardiac output was inversely correlated to peak enhancement in the right ventricle and the time to peak enhancement in the left ventricle.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations